Effect of novel cycloaliphatic comonomer on surface roughness and surface hardness of heat-cure denture base resin - Ranganathan Ajay; Karthigeyan Suma; Vikraman Rakshagan; Elumalai Ambedkar; Vellingiri Lalithamanohari; Murugesan Sreevarun (Wolters Kluwer Medknow Publications, 2020)
Background: Polymethyl methacrylate (PMMA) is a widely used resin in the field of prosthodontics for fabricating myriad orofacial prostheses. Albeit several advantages, it possesses certain lacunae concerning physicomechanical properties. Purpose: This in vitro research aimed to evaluate the surface roughness (SR) and hardness (SH) of heat-cured PMMA processed with a cycloaliphatic monomer, tricyclodecane dimethanol diacrylate (TCDDMDA), in methyl methacrylate at various concentrations. Materials and Methods: Groups have been divided into control (SRC and SHC) and experimental groups (SR10 and 20; SH10 and 20). Forty-five PMMA disc specimens were prepared. SR was assessed using a nanomechanical testing machine and the arithmetic roughness (Ra) was recorded. The same specimens were then subjected to Vicker's microhardness testing and Vicker's hardness number (VHN) was obtained. Data were compared using one-way analysis of variance (ANOVA) and post hoc Bonferroni tests (α=0.05). Results: The mean (standard deviation [SD]) of SRC, SR10, and 20 groups were 111.415 nm (0.789), 62.666 nm (0.482), and 41.004 nm (0.561), respectively. The mean (SD) VHN of SHC, SH10, and 20 groups were 21.003 (0.252), 23.975 (0.207), and 34.622 (0.079), respectively. Conclusion: The addition of TCDDMDA markedly decreased the SR and increased the SH of the experimental groups.